Integral Pressure Strip/Electrowin Circuit for Gold Recovery from Activated Carbon - Macaulay J (The Australasian Institute of Mining and Metallurgy, 1984)
The recovery of gold from cyanide liquors is frequently effected by using activated carbon. Process economics however require non destructive methods of gold extraction from the carbon so that it may be recycled.Stripping at atmospheric pressure usingthe method of Zadra et al(l) suffers from the disadvantage of unfavourable kinetics with strip times of the order of 48-72 hours. Subsequent research has led to development of processes which strip the gold more rapidly namely: A.A.R.L. process, (2,3) organic solvent (4,5,6) and pressure stripping (7,8)This paper reports on a development of the pressure stripping technique in which stripping and electrowinning are carried out at elevated temperature and pressure.